Discovery and Optimisation of Novel Bombinin-Derived Peptides from Bombina variegata against Staphylococcus aureus - Jiachen Liu; Keyi Yao; Ruize Sun; Xiaonan Ma; Chengbang Ma; Xiaoling Chen; Yangyang Jiang; Tao Wang; Tianbao Chen; Chris Shaw; Mei Zhou; Lei Wang (Probiotics and Antimicrobial Proteins, 2026)
Amphibian skin-secreted antimicrobial peptides (AMPs) have garnered significant attention for their excellent biological activity and low propensity for drug resistance over the past 40 years. Bombinins and bombinin H, two classes of AMPs isolated from the skin secretions of Bombina species, demonstrate strong antimicrobial activity against broad-spectrum microorganisms. In this study, two novel peptides, bombinin-like peptide 7S and bombinin-H2L, were identified from the toad, Bombina variegata . While both peptides exhibited broad-spectrum antimicrobial activity, they also showed relatively high cytotoxicity. To explore the structure–activity relationship and enhance therapeutic potential, bombinin-H2L, which displayed stronger average antimicrobial activity, was used as a template. With the aid of bioinformatics analysis, a series of bombinin-H2L analogues were designed by increasing the net positive charges and/or adjusting the amphiphilicity of the parent peptide. Among these analogues, [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L demonstrated high therapeutic efficacy and specificity toward clinically isolated, drug-resistant Staphylococcus aureus strains in both in vitro and ex vivo tests. Their notable biosafety profiles, sensitivity to diverse environments, and ability to disrupt biofilms highlight their potential for further development. Additionally, studies on the mechanism of [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L revealed a membrane-targeted antimicrobial mechanism, with its antibacterial function exerted by disrupting the integrity of bacterial membranes. These findings provide valuable insights into structural modifications of bombinin H peptides for enhanced activity, and [Arg 8, 15 ]BH2L and [Lys 7, 8 ]BH2L have the potential as promising candidates for novel antibacterial agents in treated bacterial skin infections.

Characterization of the marine medaka AHRs and the comparison with those of Japanese medaka in response to dioxin and additional AHR ligands - Wanglong Zhang; Yanjiao Zong; Ruize Sun; Zhenhong Xue; Wenhui Wan; Anran Ren; Yongchao Ma; Wenjing Tian; Renjun Wang (Aquatic Toxicology, 2025)

Probability Stability Evaluation of Coral Reef Limestone Reef Slopes Under Earthquake - Ruize Ma; Baifeng Ji; Longya Zhang; Shuang Pan; Kaimeng Hu (Journal of Marine Science and Engineering, 2025)
With the rapid development of island construction and the frequent occurrence of natural disasters, the stability of coral reef slopes is attracting increasing attention. This study aims to assess the dynamic stability and instability risks of coral reef slopes under different earthquake intensities. Geological data were integrated, and the Newmark method and finite element analysis were employed for probabilistic stability assessment and permanent displacement evaluation, leading to the development of a validated model for slope stability assessment. The study explored the effects of varying earthquake intensities on slope stability. Results indicate that the stratified structure significantly influences stability. Reef limestone slopes exhibited higher stability, whereas multi-layered slopes, due to looseness, were less stable. Both slope types remained stable under static conditions. Earthquake intensity substantially impacted stability, with multi-layered slopes showing instability probabilities of 48% and 100% under peak ground accelerations (PGA) of 0.3 g and 0.4 g. Under extreme seismic conditions, the permanent displacement of multi-layered coral reef slopes significantly increased. This study aims to fill the gap in previous research by incorporating the random distribution of stratigraphic parameters, conducting probabilistic stability analysis based on the random distribution of geological parameters, and thereby providing references for island reef engineering construction.

Gas-liquid interfacial reaction mechanisms of typical small α-dicarbonyls in the neutral and acidic droplets: Implications for secondary organic aerosol formation - Qiuju Shi; Ruize Ma; Yongpeng Ji; Weina Zhang; Yuemeng Ji; Taicheng An (Atmospheric Environment, 2024)

Experimental Investigation on Near-Field Acoustic Propagation Characteristics of Leakage Detection in Submarine Pipelines - Kang Zhang; Ruize Ma; Tao Geng; Jiannan Yang; Yongjun Gong (Journal of Marine Science and Engineering, 2023)
The leakage of subsea oil and gas pipelines can have adverse impacts on production progress and the ecological environment. Investigating the sound source and near-field sound propagation of pipeline leaks is essential for understanding the acoustic characteristics of and variations in these leaks. Such understanding is significant for the accurate detection and location of small leaks in pipelines. In this study, we designed an experimental system to study the characteristics of leakage sound signals. We introduced the formation mechanism of leakage sound sources and reviewed corresponding theoretical research. The leakage sound signal’s characteristic frequency range was determined to be between 1 kHz and 2 kHz. We examined the effects of pipeline pressure, leakage aperture, and detection distance on the acoustic signal characteristics. The results show that as internal pipe pressure increases, the leakage sound signal intensity first increases and then decreases. As the leakage aperture increases, the intensity of the leakage sound signal increases. Within a short distance, the intensity remains consistent regardless of detection distance. The results of this experimental study can guide the acoustic internal detection of pipelines. This study has practical significance in the timely detection of small leaks in pipelines and preventing leakage accidents from occurring.